PERANCANGAN VIDEO PEMBELAJARAN ANIMASI MENGENAI PENCEMARAN AIR PADA USIA REMAJA - Utami, Melinda; Widyastuti, Handini; Junadi, Bambang (Journal of Information System, Applied, Management, Accounting and Research, 2026)
The decline in water quality that is the impact of water pollution will greatly affect the survival and ecosystem. Lack of education causes teenagers' understanding of water pollution to be relatively low because education related to water pollution is still rarely conveyed and less interesting. Education about water pollution needs to be conveyed especially to teenagers to instill awareness of maintaining environmental conservation. This research aims to develop learning media in the form of interactive animation applications as a web-based water pollution education media. This research uses the waterfall system development method with structured and systematic stages. This application is web-based so it is easily accessible as long as it is connected to the internet and built using HTML, CSS, and Javascript. The result of this research is in the form of an interactive animation application for water pollution education with an attractive appearance with complex and effective materials as an educational medium. Based on the questionnaire that was distributed to 49 adolescent respondents with an age range of 10 to 18 years old, a positive response was obtained that the application made could be an educational media with a satisfactory response.